Genetic Polymorphism Analysis of Progression-Free Survival Rate of Prostate Cancer with Androgen Deprivation Therapy: Frequentist Network Meta-Analysis - Daryanto, Besut; Zümrütbaþ, Ali Ersin; Hakim, Lukman; Negara, Edvin; Janardhana, Alfryan; Setiawan, Ilham Rachmat; Winstonly, Brian; Neville, Neville (Universitas Brawijaya, 2026)
Various gene mutations play an essential role in the development of prostate cancer (PCa). However, the predictive impact of the HSD3B1 gene on germline and somatic status has not been adequately investigated, as such genes and multi-gene mutations have not been thoroughly discussed. Hence, this study aimed to determine the rate of progression and gene polymorphisms in Androgen Deprivation Therapy (ADT)-treated prostate cancer. Research articles were found using MeSH terms and manual entry from PubMed, ScienceDirect, and Google Scholar. The search terms for polymorphism were “SNP”,”single-nucleotide polymorphism”, “polymorphism”, “variation”, or “mutation’, and those for prostate cancer were “prostate cancer”, “prostatic neoplasm”, “cancer of prostate”, “neoplasms, prostate”, “prostate neoplasm”, and “prostatic cancer”. All related articles and abstracts were then retrieved. Papers were assessed using the Newcastle-Ottawa Scale and analysed using REVMAN 5.4. No low-quality papers were excluded from the study. All papers were reported using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Based on the search results, 2520 articles were obtained, and 8 articles were included in this review. The results of pooled log transformed HR and 95% CI as a whole were at CYP17A1 rs 17115100: HR = 1.32 (1.11-1.55); rs 2486758 : HR = 1.59 (1.44-1.75); rs 10883783 : HR = 1.27 (0.99-1.64); HSD17B4 rs 7737181 : HR = 1.11 (1.00-1.22) 95%CI ; HSD3B1 rs 1047303 : HR = 1.57 (1.24-1.99); SRD5A2 rs 523349 : HR = 95% CI. SRD5A2 rs 523349, HSD3B1 rs 1047303, and CYP17A1 rs 2486758 had high significance values on HR progression free survival. SRD5A2 rs523349 is the most influential factor in the progression survival rate of patients administered with ADT.